General characteristics affective disorders in arterial hypertension - A. A. Tolmachov (Kazimierz Wielki University, 2016)
The author analyzes researches on the study of affective disorders in arterial hypertension (AH). It is noted that AH at the present stage is considered as one of the factors of cognitive dysfunction. The article emphasizes that the analysis of comorbid relations of depression and hypertension is hardly possible without the study of affective and cardiovascular disorders at the clinical level, taking into account their dynamic characteristics and key features of the course of depressive states in general. The author considers the features of the current: post-stroke depressions, nosogenic depressions of anxious and anxious-hypochondriacally types, anxiety-phobic disorders, comorbid panic disorders, protracted depression with traits of endoreactive dysthymia, hypochondriacal disorders, panic attacks, and the like in patients with arterial hypertension. Some features of affective disorders are revealed in patients with cardiovascular disorders. It is emphasized that the increase in the effectiveness of treatment of mental disorders in patients with hypertensive encephalopathy can be solved by improving the methods of early diagnosis, developing additional screening and monitoring diagnostic tools using it in an interdisciplinary approach.